Crusher machine design for plastic bottle cap waste recycling process to support sustainability - Herry Syaifullah; Indra Setiawan; Albertus Aan Dian Nugroho; Dinda Lutfiah; Dwima Septiar Priambada; Arka Baswara Bimo Sakti (LPPMPK- Universitas Muhammadiyah Cileungsi, 2026)
The problem of plastic waste in Indonesia is becoming increasingly urgent every day due to the increase in plastic consumption. The increasing number of plastic bottle caps will have a negative impact on the environment. This problem can be overcome by converting this waste into economically valuable products. One effective solution is recycling, but the current obstacle is the lack of effective tools to optimally crush plastic bottle cap waste. Therefore, it is necessary to design and manufacture a special crusher machine to process plastic bottle cap waste. This study aims to develop a crusher machine specifically designed to process plastic bottle cap waste to support sustainable recycling. . The purpose of this research is to develop innovative technology for crushing plastic bottle cap waste. The method used in this research is the CDIO approach, the research includes stages of problem identification, machine design, prototype fabrication, and performance testing. Several improvements were implemented, including blade geometry modification, addition of a secondary shaft, gear reducer ratio adjustment, and frame redesign for safety enhancement. Test results show that the prototype effectively crushes various types of plastic caps, with improved cutting speed after modifying the gear reducer from 1:30 to 1:20 and adding forked blades. This development supports the recycling industry by providing a more efficient and reliable plastic crushing process. The purpose of this research is to develop innovative technology for crushing plastic bottle cap waste. The method used in this research is the CDIO (Conceive, Design, Implement, Operate) approach, starting from problem identification, design, prototyping, and performance testing. Several innovations were made, such as modifying the shape and thickness of the cutting blade, adding a shaft, changing the gear reducer ratio, and improving the frame design to increase safety and efficiency. The test results showed that the machine can crush various types of plastic, such as bottles and gallon caps, effectively. Changing the gear reducer ratio from 1:30 to 1:20 increased the rotation speed, while modifying the blade to form a branch accelerated the crushing process. This research is important to meet the needs of the industry that continues to grow along with technological advances, so that the process of recycling plastic bottle cap waste can run more efficiently.